150th Anniversary Series: Desmosomes and the Hallmarks of Cancer. (2nd January 2015) - Huber, Otmar; Petersen, Iver
Abstract: Desmosomes represent adhesive, spot-like intercellular junctions that in association with intermediate filaments mechanically link neighboring cells and stabilize tissue architecture. In addition to this structural function, desmosomes also act as signaling platforms involved in the regulation of cell proliferation, differentiation, migration, morphogenesis, and apoptosis. Thus, deregulation of desmosomal proteins has to be considered to contribute to tumorigenesis. Proteolytic fragmentation and downregulation of desmosomal cadherins and plaque proteins by transcriptional or epigenetic mechanisms were observed in different cancer entities suggesting a tumor-suppressive role. However, discrepant data in the literature indicate that context-dependent differences based on alternative intracellular, signal transduction lead to altered outcome. Here, modulation of Wnt/β-catenin signaling by plakoglobin or desmoplakin and of epidermal growth factor receptor signaling appears to be of special relevance. This review summarizes current evidence on how desmosomal proteins participate in carcinogenesis, and depicts the molecular mechanisms involved.